2021
DOI: 10.3389/fimmu.2021.764749
|View full text |Cite
|
Sign up to set email alerts
|

TC2N: A Novel Vital Oncogene or Tumor Suppressor Gene In Cancers

Abstract: Several C2 domain-containing proteins play key roles in tumorigenesis, signal transduction, and mediating protein–protein interactions. Tandem C2 domains nuclear protein (TC2N) is a tandem C2 domain-containing protein that is differentially expressed in several types of cancers and is closely associated with tumorigenesis and tumor progression. Notably, TC2N has been identified as an oncogene in lung and gastric cancer but as a tumor suppressor gene in breast cancer. Recently, a large number of tumor-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 134 publications
(149 reference statements)
0
7
0
Order By: Relevance
“…Over the years, previous studies have identi ed numerous tumor suppressor genes that play a crucial role in regulating cell growth and preventing the progression of cancer [21] . Tumor suppressor genes can serve as biomarkers for cancer diagnosis [22] and prognosis [23] and as targets for therapies [21] . Recent studies have explored the value of RBP7 in anticancer [20] and tamoxifen resistance [19] in HR + BC.…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, previous studies have identi ed numerous tumor suppressor genes that play a crucial role in regulating cell growth and preventing the progression of cancer [21] . Tumor suppressor genes can serve as biomarkers for cancer diagnosis [22] and prognosis [23] and as targets for therapies [21] . Recent studies have explored the value of RBP7 in anticancer [20] and tamoxifen resistance [19] in HR + BC.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 The mechanistic relationship between these observations is currently unclear, and a function for TC2N beyond its known role in tumorigenesis is unknown. 75 In a pediatric study of severe HA subjects, the TC2N variant rs10133762 was associated with a slower rate of FVIII clearance. 9 However, this association was not statistically significant in adult or mixed adolescent and adult populations.…”
Section: Variants In Vwf-fviii and Fviii Clearance Receptorsmentioning
confidence: 99%
“…These results showed that BAZ2A expression in uenced prognosis in several cancers and that BAZ2A gene expression may serve as a diagnostic marker in some cancers. 4.Genetic alterations are correlated with DNA methylation of the BAZ2A promoter.…”
Section: The Association Between Baz2a Expression and Tumor Diagnosis...mentioning
confidence: 99%
“…Cancer poses a global public health challenge, with a notable surge in both the occurrence and fatality rates of this disease [1,2]. Remarkable progress has been achieved in the advancement of cancer treatment strategies, but the e cacy of treatment and prognosis of cancer patients are still not ideal because of drug resistance and the potential adverse effects of drugs [3].Hence, further investigation of the pathogenesis of cancer is critical to develop new therapies to improve patient prognosis [4].…”
Section: Introductionmentioning
confidence: 99%